The vehicle loading problem with a heterogeneous transport fleet. (July 2016) - Liu, Jiansheng; Smith, Alice E.; Qian, Dan
Highlights: This paper is the first to model and solve the vehicle loading problem with a heterogeneous fleet. An efficient and effective branch and bound algorithm is developed. The method is demonstrated on a real case study from a vehicle distributor in China. Abstract: As an emerging variant of the vehicle loading problem, the heterogeneous multi-type fleet vehicle loading problem in finished vehicle logistics (HVLP–FVL) is modeled and solved. The HVLP–FVL maximizes the total profit of a vehicle fleet where different models of finished vehicles result in different profits and routing costs are considered based on distance traveled. Addressing the vehicle structures, simplified geometric models of both the finished vehicle and transport vehicle are defined. The optimization considers which finished vehicle orders to transport and then makes the loading assignment to the transport vehicles. To improve the computational performance of the traditional branch and bound algorithm, an enhancement using greedy search based on oscillation analysis is proposed. A real case study is used to evaluate the effectiveness of the improved algorithm and a series of experiments are conducted over a set of finished vehicle loading problems. The results demonstrate the proposed approach has superior performance and satisfies users in practice. Contributions of the paper are the modeling and solving of a real complex problem in vehicle manufacturing logistics and a simple branch-and-bound speed up that could be used in other problem classes.